2015
DOI: 10.3390/ijms161126045
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Promotes cPLA2 Gene Expression through Activation of the MAPK/NF-κB/p300 Cascade

Abstract: Hyperplasia or hypertrophy of adipose tissues plays a crucial role in obesity, which is accompanied by the release of leptin. Recently, obesity was determined to be associated with various pulmonary diseases including asthma, acute lung injury, and chronic obstructive pulmonary disease. However, how obesity contributes to pulmonary diseases and whether leptin directly regulates lung inflammation remains unclear. We used cell and animal models to study the mechanisms of leptin mediation of pulmonary inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 55 publications
0
17
0
1
Order By: Relevance
“…Adipose tissue is composed of adipocytes and a vascular‐stromal fraction, which contains macrophages, fibroblasts, endothelial cells, and pre‐adipocytes. In addition to the regulation of whole‐body fatty acid homeostasis, adipose tissue functions as a complex endocrine organ, secreting adipokines, such as leptin, adiponectin, visfatin, tumor necrosis factor‐α, interleukin‐6, monocyte chemotactic protein‐1, and adipocyte fatty acid‐binding protein (Hsu, Wu, Chang, & Lin, ). Leptin induces matrix metalloproteinase 7 expression to promote ovarian cancer cell invasion by activating ERK and JNK pathways (Ghasemi, Hashemy, Aghaei, & Panjehpour, ).…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue is composed of adipocytes and a vascular‐stromal fraction, which contains macrophages, fibroblasts, endothelial cells, and pre‐adipocytes. In addition to the regulation of whole‐body fatty acid homeostasis, adipose tissue functions as a complex endocrine organ, secreting adipokines, such as leptin, adiponectin, visfatin, tumor necrosis factor‐α, interleukin‐6, monocyte chemotactic protein‐1, and adipocyte fatty acid‐binding protein (Hsu, Wu, Chang, & Lin, ). Leptin induces matrix metalloproteinase 7 expression to promote ovarian cancer cell invasion by activating ERK and JNK pathways (Ghasemi, Hashemy, Aghaei, & Panjehpour, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the impaired cortisol action on PBMC of obese individuals may contribute to the enhancement in proinflammatory cytokine production and histone H4 hyperacetylation in obesity. On the other hand, in vitro data revealed that leptin increased the activation of MAPKs/NF- κ B pathway through acetylation of histone H4 [ 42 ]. As the expansion of adipose tissue in obesity is accompanied by the augmentation of leptin, we hypothesized that leptin may play a key role in H4ac status in PBMC of the obese.…”
Section: Discussionmentioning
confidence: 99%
“…Garcinol blocked the formation of high fat diet (HFD)‐induced obesity and suppressed glutamate pyruvate transaminase, cholesterol and triacylglycerol in the plasma of animals fed with garcinol . Pretreatment of leptin‐stimulated cells with garcinol (1 μM) also inhibited leptin‐associated cPLA 2 expression via inhibition of p300 HAT . In addition, garcinol displayed beneficial effects on diabetic Wistar rats and oral application of garcinol (10 mg/kg and 20 mg/kg) normalized diabetic parameters in the rats similar to the antidiabetic drug glibenclamide .…”
Section: New Effects On Inflammation Processes and Neurodegenerative mentioning
confidence: 95%
“…[75] Pretreatment of leptinstimulated cells with garcinol (1 μM) also inhibited leptin-associated cPLA 2 expression via inhibition of p300 HAT. [76] In addition, garcinol displayed beneficial effects on diabetic Wistar rats and oral application of garcinol (10 mg/kg and 20 mg/kg) normalized diabetic parameters in the rats similar to the antidiabetic drug glibenclamide. [77] Osteolysis is often based on activated osteoclasts which are bone-resorbing osteoimmune cells.…”
Section: Epilepsymentioning
confidence: 96%